On (Δm,I)-Statistical Convergence of Order α - Mikail Et; Abdullah Alotaibi; S. A. Mohiuddine (The Scientific World Journal)
The idea of I-convergence of real sequences was introduced by Kostyrko et al., (2000/01) and also independently by Nuray and Ruckle (2000). In this paper, we introduce the concepts of (Δm,I)-statistical convergence of order α and strong (Δpm,I)-Cesàro summability of order α of real sequences and investigated their relationship.